A Multiplex SYBR Green Real-Time PCR Assay for the Detection of Three Colistin Resistance Genes from Cultured Bacteria, Feces, and Environment Samples - Li, Jiyun; Shi, Xiaomin; Yin, Wenjuan; Wang, Yang; Shen, Zhangqi; Ding, Shuangyang; Wang, Shaolin (Frontiers in Microbiology, 2017)
The aim of the study was to develop a multiplex assay for rapid detection of mcr-1, mcr-2, and mcr-3, a group of genes of conferring resistance to colistin mediated by plasmid in Enterobacteriaceae. A SYBR Green based real-time PCR assay has been designed to detect the mcr genes, and applied to cultured bacteria, feces and soil samples. All three mcr genes could be detected with a lower limit of 102 cultured bacteria. This test was highly specific and sensitive, and generated no false-positive results. The assay was also conclusive when applied to feces and soil samples containing mcr-1-positive Escherichia coli, which could facilitate the screening of mcr genes not only in the bacteria, but also directly from the environment. This simple, rapid, sensitive and specific multiplex assay will be useful for rapid screening of the colistin resistance in both clinical medicine and animal husbandry.